Conflictology and Role of State Institutions in Federalism: A Study on Gorkhaland and Balochistan - Shahzad Ali Gill; Saba Javaid; Muhammad Hamid Murtza; Sarfraz Batool; Sidra Jamil (Journal of Management Practices, Humanities and Social Sciences, 2021)
Conflicts are a common phenomenon in today’s disorderly world. Ethnic conflicts usually arise in multi-ethnic, pluralistic, or democratic societies. While employing institutional theory, this qualitative study explores the role of institutions in escalating and de-escalating ethnic conflicts through analysis of Gorkhaland and Balochistan ethnic conflicts in India and Pakistan, respectively. Both conflict-prone regions hold significant geo-strategic importance for their countries and share common grievances ranging from political marginalization, identity crisis, structural inequalities, denial of democracy, and enduring state antagonism. Since federalism is considered a golden road towards sustainable ethnic peace, a deep understanding of both conflicts’ nature, synthesis, underpinning factors, and the contemporary situation is pivotal for advancing informed political discourse. The study follows a desk research method for data collection and a descriptive approach for synthesizing the facts gathered from secondary sources, including the grey literature. The study informs that the suppression of dissenting voices doesn’t resolve ethnic conflicts instead adds insult to injuries. The study concludes that as long as the non-democratic policies of the governments are in place, this ethno-regional agenda would continue to be a significant issue in the politics of both federal states – India and Pakistan. The study implies that both countries should volte-face their state policy towards their respective conflict-prone regions to sustain a socially cohesive, economically viable, and politically stable society. The study also presents several contributions coupled with limitations and future research directions.